Election polls in Brazil: Trends and performance - Meireles, Fernando; Russo, Guilherme (Estudos Avançados, 2022)
This paper compares the results of more than two thousand pre-electoral polls between 2012 and 2020 with the official electoral results in five Brazilian elections. We examine the effects of random and non-random factors, such as sample size and the time before the elections, on differences between the polls’ estimates and the ballot results. Among other findings, we show that later polls, conducted just before the election, with large samples, are better at minimizing errors. We also document that polls for presidential and gubernatorial elections and second-round elections exhibit lower error rates. Taken together, our results suggest that Brazilian pre-electoral polls perform similarly to polls conducted in other countries.